Mechanics and dynamics of helical milling operations - Liu, Changyi (Strojniški vestnik, 2014)
This paper presents analytical models dealing with time domain cutting forces and the time and frequency domain dynamics of helical milling operations. The cutting forces both on the side-cutting edges and on the end-cutting edges along the helical feed path are modelled by considering the tangential and the axial motions of the tool. The dual periodicity, which is caused by the spindle rotation, as well as the period of the helical feed of the cutting tool has been included. The models of the machining process dynamics and of the chatter stability problems are decomposed into two parts: the critical axial depth of cut, and the critical radial depth of cut, both of which are solved. The dynamics model allows the selection of processing parameters, including axial cutting depth, radial cutting depth, and spindle rotation velocity in the chatter-free zone and the prediction of chatter vibrations during helical milling. Experiments have also been performed for real machining observations in order to verify the chatter-free zone obtained from the analytical model.
Keywords: dinamika rezanja; drdranje; modeliranje; načrtovanje procesa; odrezavanje; rezalne sile; rezkanje po vijačnici